A regional citrate anticoagulation protocol for pre-dilutional CVVHDf: The 'Modified Alabama Protocol' - Davies, Hugh (Elsevier Inc, 2008)
The use of citrate to anticoagulate the Continuous Renal Replacement Therapy (CRRT) circuit has not been widely adopted in Australia as an alternative to heparin due to treatment complexity and risks of metabolic complications and availability of suitable solutions. However, interest persists in citrate anticoagulation as a viable alternative when heparin is either contraindicated or has failed to provide an adequate circuit lifespan due to dialyser clotting.This paper describes a practical protocol for the delivery of regional citrate anticoagulation for pre-dilutional CVVHDf. The protocol maintains the flexibility in dialysis/ haemofiltration dose prescription and advises on the requirement for monitoring and necessary adjustments to prevent the development of metabolic disturbances. This may assist regional citrate to achieve wider acceptance as an alternative anticoagulation strategy for critically ill patients.